2021
DOI: 10.3390/app11114821
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Medication-Related Osteonecrosis of the Jaws amongst Dental Professionals in Poland

Abstract: Background: Medication-Related Osteonecrosis of the Jaws (MRONJ) is a serious complication of antiresorptive therapy. The aim of the study was to assess the level of knowledge and awareness regarding MRONJ among Polish dentists and students of dentistry. Methods: The online self-administered questionnaire was sent out electronically among dentists in Poland and dentistry students of the Medical University of Gdansk. The results obtained were statistically analyzed. The results were considered statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…However, this proportion is very small compared with other studies, such as the findings of [24]. In contrast, 94.6% of individuals in another study indicated they knew the term MRONJ [25]. The variance in awareness levels between studies could be attributed to several factors, including differences in the study populations, sampling methods, geographical locations, survey instruments employed, or the timing of data collection.…”
Section: Discussionmentioning
confidence: 66%
“…However, this proportion is very small compared with other studies, such as the findings of [24]. In contrast, 94.6% of individuals in another study indicated they knew the term MRONJ [25]. The variance in awareness levels between studies could be attributed to several factors, including differences in the study populations, sampling methods, geographical locations, survey instruments employed, or the timing of data collection.…”
Section: Discussionmentioning
confidence: 66%